Association Between Refractive Errors and Heterotropia: A Counter Check - Hijaz Ijaz, Syeda Rushda Zaidi Mohammad Ali A Sadiq, Asad Aslam Khan (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine an association between refractive errors and heterotropia. Study Design: Cross sectional study. Place & Duration of Study: Orthoptic clinic Mayo hospital Lahore from October 2015 to December 2015. Material & Methods: Data was collected from College of Ophthalmology and Allied Vision sciences, Eye OPD pediatrics clinic Mayo Hospital Lahore using a non-probability convenient sampling technique. Visual acuity of patients was recorded using VLC monitor at distance in decimal notation. Refractive error and Orthoptic assessment of the patients was later recorded for further analysis. Results: A sample of 100 patients with heterotropia up to the age of 40 years was analyzed. The random composition of the male and female objects in the study was estimated to be 42% and 58% respectively. It was observed that hyperopia and hyperopic astigmatism were more prevalent in esotropia and emmetropia while myopia and myopic astigmatism were more common in exodeviations. The (p-value ? 0.000) confirmed an association between Refractive error and Heterotropia. Conclusion: There is a strong association between Refractive error and Heterotropia. Key Words: Refractive Errors, Heterotropia, Hyperopic Astigmatism.